A cross-sectional study on malnutrition in elderly using mini nutrition assessment scores in an urban slum - Sonawane, Sharon Samson; Varghese, Varsha Anna; Moses, John Paul Jetpole (International Journal Of Community Medicine And Public Health, 2019)
Background: The global demographic shift presents new challenges regarding health of elderly. Nutrition in elderly affects their immunity and functional ability. Most cases of malnutrition in elderly go under-reported. Hence, this study was conducted to study malnutrition in elderly using MNA score with the aim to find out the prevalence of malnutrition in elderly and study its associated factors in an urban slum in the field practice area of parent medical college. Methods: Study was conducted in 120 elderly (>60 years) study participants. A pre-tested semi-structured questionnaire consisting of information on lifestyle, somatic, functional, social factors and Mini Nutrition Assessment (MNA)questionnaire was administered to assess the nutritional status of the elderly. Descriptive statistical measures like percentage, mean, standard deviations and inferential statistical measure like chi square were calculated. Results: Among 120 elderly study participants, 83 (69.17%) were females, 37 (30.83%) were male and their mean age was 67.21 (±6.27) years. 40 (33.33%) had malnutrition, 65 (54.17%) were at risk of malnutrition and 15 (12.5%) had satisfactory nutrition. Medication use, socio-economic status and marital status showed significant association with malnutrition in elderly. Conclusions: The high prevalence of malnutrition and risk of malnutrition in elderly necessitates appropriate preventive and corrective measures like detailed evaluation, regular follow-up and dietary interventions to be undertaken to deal with malnutrition in elderly.